2012
DOI: 10.1038/leu.2012.341
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes can be effectively recruited for ex vivo and in vivo lysis of AML blasts by a novel CD33/CD3-bispecific BiTE antibody construct

Abstract: Patients with acute myelogenous leukemia (AML) are in high need of novel targeted therapies. Here we explored the ex vivo activity of AMG330, a novel T-cell-engaging BiTE (bi-specific T-cell engagers) antibody (Ab) construct, that is bispecific for the myeloid differentiation antigen, CD33 and CD3, in primary samples from AML patients (N=23) and AML cell lines. KG-1 and U937 cells were lysed in co-culture with healthy donor T-cells at AMG330 concentrations as low as 0.1 ng/ml (1.8 pM). T-cells derived from AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 37 publications
4
80
0
3
Order By: Relevance
“…12,13 As prior in vitro investigations of the cytotoxic effect of AMG 330 demonstrated that the T cell killing of targets increased over time, 11 we first screened for activity at 24 hours. At this time point, very little specific cytotoxicity could be detected even at higher doses of AMG 330 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 As prior in vitro investigations of the cytotoxic effect of AMG 330 demonstrated that the T cell killing of targets increased over time, 11 we first screened for activity at 24 hours. At this time point, very little specific cytotoxicity could be detected even at higher doses of AMG 330 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…14 We used HL-60, ML-1, NB4, and TF-1 cells as additional models because of their CD33 expression and, in the case of HL-60, ML-1, and NB4 cells, our previous studies showing sensitivity to CD33-targeted therapy with GO. 12,13 As prior in vitro investigations of the cytotoxic effect of AMG 330 demonstrated that the T cell killing of targets increased over time, 11 we first screened for activity at 24 hours. At this time point, very little specific cytotoxicity could be detected even at higher doses of AMG 330 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMG 330 has previously shown robust ex vivo activity in peripheral blood mononuclear cell (PBMC) samples from patients with AML by redirecting autologous T cells for lysis of AML blasts at low endogenous effector-to-target (E:T) ratios (18). Here, we have characterized AMG 330 in detail for its dual binding activity, CD33 epitope recognition, stability in serum, cross-reactivity with a non-human primate species, potency of redirected lysis of multiple human AML cell lines, potency at reduced E:T ratios, sensitivity toward shed CD33, T-cell activation, and impact of intravenously (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…15 However, in spite of these limitations, the agent produced clear clinical benefits, including long-lasting treatment successes in particular after administration in fractionated doses to limit toxicity, probably due to its ability to eliminate some of the relapse-initiating LSCs. 16,17 Another CD33-directed antibody-drug conjugate, SGN-CD33A (Vadustuximab Talirine), is in clinical development, 18,19 as well as bispecific T cell engagers (BiTEs; AMG 330 and others), 2024 and tetravalent tandabs targeting CD33 and engaging T cells as cytolytic effectors (AMV 564). 25 Finally, genetically engineered T cells equipped with transgenic chimeric antigen receptors (CARs) specific for CD33 showed anti-leukemic efficacy in xeno-transplanted mice and were tested in an AML-patient.…”
Section: Introductionmentioning
confidence: 99%